THEORETICAL FOUNDATIONS OF CODE-SWITCHING IN SOCIOLINGUISTICS AND INTERNET DISCOURSE - M.Kh. Temirova (International Journal of Literature and Language Studies, 2026)
This article examines the theoretical foundations of code-switching in sociolinguistics and Internet discourse. The study analyzes the evolution of the concept of code-switching from Roman Jakobson’s theory of communication to contemporary sociolinguistic approaches developed by Blom and Gumperz, Poplack, Fishman, and Myers-Scotton. Particular attention is paid to the role of code-switching in digital communication, where multilingual users actively combine different linguistic and semiotic resources, including languages, registers, emojis, GIFs, and memes. The paper discusses the main types of code-switching, including situational, metaphorical, inter-sentential, intra-sentential, and intra-word switching, as well as their communicative and social functions. The analysis demonstrates that code-switching in Internet discourse serves not only as a linguistic phenomenon but also as an important tool for expressing identity, managing interpersonal relations, conveying emotions, and participating in global digital communities. The findings highlight the significance of code-switching as a key mechanism of communication in multilingual online environments and contribute to a deeper understanding of language behavior in contemporary digital discourse.